In vitro liver models for toxicological research - Fukunaga, Ichiro; Takebe, Takanori (Drug metabolism and pharmacokinetics, 2025)
Drug-induced liver injury (DILI) presents a major challenge not only in new drug development but also in post-marketing withdrawals and the safety of food, cosmetics, and chemicals. Experimental model organisms such as the rodents have been widely used for preclinical toxicological testing. However, the tension exists associated with the ethical and sustainable use of animals in part because animals do not necessarily inform the human-specific ADME (adsorption, dynamics, metabolism and elimination) profiling. To establish alternative models in humans, in vitro hepatic tissue models have been proposed, ranging from primary hepatocytes, immortal hepatocytes, to the development of new cell resources such as stem cell-derived hepatocytes. Given the evolving number of novel alternative methods, understanding possible combinations of cell sources and culture methods will be crucial to develop the context-of-use assays. This review primarily focuses on 3D liver organoid models for conducting. We will review the relevant cell sources, bioengineering methods, selection of training compounds, and biomarkers towards the rationale design of in vitro toxicology testing.